1996
DOI: 10.1007/bf00144423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C viruses infection in chronic alcoholics with or without liver disease in Ioannina, Greece: Low incidence of HCV infection

Abstract: Intravenous heroin abusers comprise a high risk group for hepatitis B and C viruses (HBV and HCV) infection. Chronic alcoholics with liver disease (LD) also comprise a high risk group for HBV infection whereas the frequency of antibodies to HCV (anti-HCV) ranges from 27-42.6%. In this study, HBV and HCV infection markers were determined in alcoholic patients with (83 patients) or without LD (68 patients) in order to assess the prevalence of these markers (HBsAg, HBsAb, HBcAb and anti-HCV). The reason for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
(42 reference statements)
0
6
0
4
Order By: Relevance
“…This study showed that, in our region of Northwestern Greece, approximately 16 percent of the donor population had serologic markers of past or current HBV infection. Taking into account our previous studies, 31,42,43 this finding indicates that the Epirus region still has a moderate prevalence of HBV infection markers (when these markers were examined in total). However, the prevalence of HBsAg carriers appears to have declined significantly in the region, from 3.5 percent (n = 1936; 95% CI, 2.7‐4.3%) in 1978 through 1982 (Kolaitis N, written communication, April 1999) to 2.1 percent (n = 1342; 95% CI, 1.33‐2.86%) in 1985 through 1992 31,42,43 and to 0.85 percent at the time of this writing (95% CI, 0.6‐1.1%) (p<0.0001 and p<0.001, respectively).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This study showed that, in our region of Northwestern Greece, approximately 16 percent of the donor population had serologic markers of past or current HBV infection. Taking into account our previous studies, 31,42,43 this finding indicates that the Epirus region still has a moderate prevalence of HBV infection markers (when these markers were examined in total). However, the prevalence of HBsAg carriers appears to have declined significantly in the region, from 3.5 percent (n = 1936; 95% CI, 2.7‐4.3%) in 1978 through 1982 (Kolaitis N, written communication, April 1999) to 2.1 percent (n = 1342; 95% CI, 1.33‐2.86%) in 1985 through 1992 31,42,43 and to 0.85 percent at the time of this writing (95% CI, 0.6‐1.1%) (p<0.0001 and p<0.001, respectively).…”
Section: Discussionmentioning
confidence: 59%
“…Taking into account our previous studies, 31,42,43 this finding indicates that the Epirus region still has a moderate prevalence of HBV infection markers (when these markers were examined in total). However, the prevalence of HBsAg carriers appears to have declined significantly in the region, from 3.5 percent (n = 1936; 95% CI, 2.7‐4.3%) in 1978 through 1982 (Kolaitis N, written communication, April 1999) to 2.1 percent (n = 1342; 95% CI, 1.33‐2.86%) in 1985 through 1992 31,42,43 and to 0.85 percent at the time of this writing (95% CI, 0.6‐1.1%) (p<0.0001 and p<0.001, respectively). This decline may suggest improvement in the general measures of HBV prevention in our region, although the previous, retrospective studies investigated a small number of donors and the methods of HBsAg detection were the same only during the second period cited above.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, a published survey of HBV and HCV infection markers from a referral center of Northern Greece among alcoholics with chronic liver disease, alcoholics without chronic liver disease, hospitalized non-alcoholic patients and healthy controls, reported an HBsAg prevalence rate of 10.8%, 7.4%, 1.4% and 2.1%, an HBcAb prevalence rate of 39.2%, 36.4%, 14.3% and 19.5% and an anti-HCV prevalence rate of 1.2%, 1.4% 0% and 0.6% respectively [12]. The prevalence rates of HBV viral markers in the non-alcoholic hospitalized patients are lower than ours while our figures come closer to the ones reported in their healthy control group.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, significantly higher prevalence of HBV infection is observed in chronic alcoholic patients—with or without established liver disease—compared to healthy blood donors or nonalcoholic hospitalized patients, which is ascribed to their specific and some times unexpected behavior [25]. …”
mentioning
confidence: 99%